Effects of compound water retention agent on soil nutrients and soil microbial diversity of winter wheat in saline-alkali land - Yunshuo Xu; Yu Gao; Wubo Li; Shuang Chen; Yajun Li; Yan Shi (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Water retention agents have been applied to agricultural fields to improve the growing conditions of crops, but the potential of these agents in saline soils is poorly understood. The effects of compound water retention agents on nutrient content and soil microbial diversity of saline winter wheat soils were investigated in a field experiment with no water retention agent (CK) and 30 kg hm2 of commercial attapulgite water retention agent (T4) as control and different amounts of compound water retention agents as treatments (15 kg hm2-T1, 30 kg hm2-T2, 45 kg hm2-T3). The study showed that the application of water retention agents increased the soil water content. From anthesis to harvest stage, the decreases in soil alkali-hydrolyzed nitrogen, available phosphorus, available potassium and organic matter content were greater in T2 and T3 than in the other treatments. At harvest stage, the alkali-hydrolyzed nitrogen content of T2 was significantly lower than that of CK and T4 6.19–8.83% and 4.62–5.39%, respectively. The soil available phosphorus content of T2 was significantly lower than that of CK 8.14–8.83%. The relative abundance of Actinobacteria, Proteobacteria and Acidobacteria as well as the Shannon and Simpson indices of T2 reached their maximum at harvest stage. T2 showed the best performance in terms of overall number of OTUs. The compound water retention agent may regulate soil nutrient content and accelerate plant nutrient accumulation by regulating soil water content and soil microbial abundance composition. Graphical abstract